2006
DOI: 10.1007/s10654-006-9045-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic variation in the leptin gene promoter and the leptin receptor gene on obesity risk in a population-based case-control study in Spain

Abstract: There are no good genetic markers for incorporating the study of genetic susceptibility to obesity in epidemiological studies. In animal models, the leptin (LEP) and the leptin receptor (LEPR) genes have been shown to be very important in obesity because leptin functions as a negative feedback signal in regulating body-weight through reducing food intake and stimulating energy expenditure. In humans, several polymorphisms in these genes have been described. However, their association with obesity is still very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
56
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 50 publications
9
56
3
1
Order By: Relevance
“…In literature, both alleles of these SNPs have been reported as risk alleles for type 2 diabetes and obesity, and a metaanalytic study reported nonsignificant associations. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]48 Consequently, additional studies in larger populations need to be carried out, to verify the involvement of these coding LEPR SNPs in the 'fetal insulin hypothesis'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, both alleles of these SNPs have been reported as risk alleles for type 2 diabetes and obesity, and a metaanalytic study reported nonsignificant associations. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]48 Consequently, additional studies in larger populations need to be carried out, to verify the involvement of these coding LEPR SNPs in the 'fetal insulin hypothesis'.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we therefore examined the effect of common SNPs in LEP and LEPR on birth weight and adult metabolic risk factors for type 2 diabetes measured in young twins recruited from the East Flanders Prospective Twin Survey (EFPTS). The SNPs studied have previously been associated with type 2 diabetesrelated traits in other populations, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and are either nonsynonymous or located in a region that might be of importance in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin regulates body weight through reducing food intake and stimulating energy expenditure. Polymorphisms in the LEPR gene may contribute to weight gain in young Dutch, 31 resting metabolic rate and substrate oxidation during low-intensity exercise in Canadians, 32 obesity in a Mediterranean 33 and Brazilian populations, 34 and 24-h TEE in Pima Indians. 35 Our signal on chromosome 9 for PROOX duplicates previous genetic findings related to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic associations may not only differ between ethnic groups, but also within. In Europe, there may be differences in genetic and other risk factors between northern and southern countries (e.g., multiple sclerosis, breast and other cancers, lipids), which asks for gene-disease association studies in specific populations, e.g., [16,17] also because true genetic heterogeneity between populations may later impact the global applicability of predictive genetic tests. Because gene-gene and geneenvironment interactions have not been extensively studied to date, further major advances in unraveling the genetic basis of common diseases may certainly be expected.…”
mentioning
confidence: 99%